1928
DOI: 10.1111/j.1151-2916.1928.tb16178.x
|View full text |Cite
|
Sign up to set email alerts
|

METHODS FOR TESTING CRAZING OF GLAZES CAUSED BY INCREASES IN SIZE OF CERAMIC BODIES1

Abstract: Investigations to determine the causes of a type of crazing which develops on certain glazed ceramic wares, some time after firing, revealed the fact that in many cases such crazing is caused by an expansion of the body. This is probably due to the combination of water with the body, while the glaze remains practically constant in size. A body may be tested for this type of crazing by placing the glazed specimens in an autoclave and subjecting them to a steam pressure of 150 to 175 pounds per square inch for o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
3

Year Published

1932
1932
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(12 citation statements)
references
References 0 publications
0
9
0
3
Order By: Relevance
“…He demonstrated that the magnitude of moisture expansion varies from one ceramic material to another, and later showed that additions of magnesite reduced moisture expansion . Even at this early stage, it was evident that the combined water was tenaciously bound, and Schurecht suggested that to see by how much an old ceramic had expanded during its lifetime, its contraction after re‐heating to 600°C should be measured. Furthermore, these long‐term moisture expansions are often in the range 0.05%–0.20% linear strain, a considerable deformation in such stiff materials, and the cause of large stresses when constrained.…”
Section: Moisture Expansionmentioning
confidence: 98%
See 1 more Smart Citation
“…He demonstrated that the magnitude of moisture expansion varies from one ceramic material to another, and later showed that additions of magnesite reduced moisture expansion . Even at this early stage, it was evident that the combined water was tenaciously bound, and Schurecht suggested that to see by how much an old ceramic had expanded during its lifetime, its contraction after re‐heating to 600°C should be measured. Furthermore, these long‐term moisture expansions are often in the range 0.05%–0.20% linear strain, a considerable deformation in such stiff materials, and the cause of large stresses when constrained.…”
Section: Moisture Expansionmentioning
confidence: 98%
“…Moisture expansion is the widely used term to describe the slow, continuing expansion of fired clay. Systematic studies began in 1928 with Schurecht, who attributed it to the uptake of what he called combined water. He demonstrated that the magnitude of moisture expansion varies from one ceramic material to another, and later showed that additions of magnesite reduced moisture expansion .…”
Section: Moisture Expansionmentioning
confidence: 99%
“…Em 1928 Schurecht [11], estudando o gretamento retardado de corpos cerâmicos esmaltados, foi o pioneiro na utilização de ensaio em autoclave para acelerar a expansão das peças cerâmicas, concluíndo que o gretamento retardado devia-se à expansão do corpo cerâmico e não a falha por fadiga do vidrado, evidenciando também a existência de correlações entre a expansão de corpos cerâmicos autoclavados e sua expansão natural. Dando continuidade às pesquisas iniciadas em 1928, Schurecht e Pole [20] foram pioneiros no estudo do efeito da composição dos corpos cerâmicos na sua EPU, tendo observado a influência de silicatos amorfos no aumento da EPU e da adição de aditivos, como carbonatos de cálcio e magnésio, na sua redução.…”
Section: Breve Históricounclassified
“…Essa hipótese foi desconsiderada [11], quando se comprovou que eram as alterações das dimensões do corpo cerâmico quem provocavam o gretamento retardado. Posteriormente [12] várias composições de vidrados (algumas comerciais) foram analisadas durante cinco anos, comprovando-se que, se os corpos cerâmicos forem mantidos fora do alcance da umidade não há alterações nas suas dimensões e nem gretamento retardado.…”
unclassified
“…Por isso essa técnica vem sendo utilizada sistematicamente para determinação da EPU em empresas e laboratórios de pesquisa. Todavia, desde a década de 30 [22] a expansão térmica é utilizada na determinação da EPU de materiais cerâmicos, tendo esta técnica adquirido maior evidência com o desenvolvimento de equipamentos que possibilitem uma maior precisão nos resultados. Vale salientar que uns dos primeiros trabalhos a utilizar a dilatometria para o estudo da EPU de massas cerâmicas comerciais se deu na década de 60 [23].…”
Section: Determinação Da Expansão Por Umidadeunclassified